EVALUATION OF SUITABILITY TRANSFER OF SMART AGRICULTURE IN IRAQI AGRICULTURAL SYSTEMS - & Taha, Naji (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The current research was aimed to evaluation of suitability  the transfer of smart agriculture in Iraqi agricultural systems so. identifying weaknesses and reasons Identifying proposals for improvement. The input evaluation process consisted of four stages: First Stage: Determination of the set of criteria which the dissemination of the smart agriculture method should be made in the light.. Second Stage: Presentation of evaluation suitable criteria the transfer of the smart agriculture method in the agricultural systems of Iraq in its preliminary form to a group of experts . to express their opinion in the field and items of the proposed criteria and the required amendments for the purpose of finalizing those criteria. Third stage: Surveying of within the work area . Fourth stage: Compare between criteria and surveying , and Judgment .The research concluded that most evaluation suitable criteria are compatible with the transfer of smart agriculture in Iraqi agricultural systems as being partially applied.